Pengaruh Kebudayaan Populer Terhadap Visual Sampul Aalbum Musik - Citra Kemala Putri (Universitas Informatika dan Bisnis Indonesia, 2020)
Mass culture and popular culture is one of the important phenomena that was born after the postmodern era. In a society that lives in the midst of mass culture and popular culture, will grow consumer communities that produce new cultural symbols and activities. This discourse then influenced various aspects, for example, the emergence of popular music and popular art movements which soon became a commodities that was consumed by many youth people. This study discusses the influence of popular culture on the visuals of music album covers which take several album covers of international musicians from different time periods as samples to compare the similarities or friction caused by various art developments as their response toward happening trends. This study uses qualitative method. This study of various visual images was considering the aesthetic idioms of postmodernism, including Pastiche, Parody, Kitsch, Camp and Schizophrenia, as well as the concepts of several art movements, such as Pop Art and Lowbrow Art. The final result of this study reveal that several music albums using the Pop Art and Lowbrow Art style contained postmodern aesthetic idioms. Each album cover can contain one or several aesthetic idioms simultaneously.